Significant linkage at chromosome 19q for otitis media with effusion and/or recurrent otitis media (COME/ROM) - Chen Fang; Mychaleckyj Josyf C; Allen E Kaitlynn; Chen Wei-Min; Hou Xuanlin; Rich Stephen S; Daly Kathleen A; Sale Michèle M (BMC, 2011)
Abstract Background In previous analyses, we identified a region of chromosome 19 as harboring a susceptibility locus for chronic otitis media with effusion and/or recurrent otitis media (COME/ROM). Our aim was to further localize the linkage signal and ultimately identify the causative variant or variants. We followed up our previous linkage scan with dense SNP genotyping across in a 5 Mb region. A total of 607 individuals from 139 families, including 159 affected sib pairs and 62 second-degree affected relative pairs, were genotyped at 1,091 SNPs. We carried out a nonparametric linkage analysis, modeling marker-to-marker linkage disequilibrium. Results The maximum log of the odds (LOD) score increased to 3.75 (P = 1.6 × 10-5) at position 63.4 Mb, with a LOD-1 support interval between 61.6 Mb and 63.8 Mb, providing significant evidence of linkage between this region and COME/ROM. The support interval contains over 90 known genes, including several genes involved in the inflammasome protein complex, a key regulator of the innate immune response to harmful exogenous or endogenous stimuli. Parametric linkage analysis suggests that for a sib of an affected individual, the recurrence risk of COME/ROM due to this linkage region is twice the recurrence risk in the population. We examined potential associations between the SNPs genotyped in this region and COME/ROM, however none provided evidence for association. Conclusion This study has refined the 19q region of linkage with COME/ROM, and association results suggest that the linkage signal may be due to rare variants.